2021
DOI: 10.3399/bjgpo.2021.0072
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on the mental health of Singaporean GPs: a cross-sectional study

Abstract: BackgroundCovid-19 has stressed healthcare systems and workers worldwide. General practitioners (GPs), as first points-of-contact between suspected cases and the healthcare system, assume frontline roles in this crisis. While the prevalence of mental health problems and illnesses arising in healthcare workers (HCWs) from tertiary care settings during Covid-19 is well-examined,(1) the impact on GPs remains understudied.AimTo describe the prevalence and predictors of anxiety, burnout, depression, and post-trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 58 publications
3
18
0
1
Order By: Relevance
“…All the items were rated on a four-point scale scoring from 0 (not at all) to 3 (nearly every day). The total score ranges from 0 to 21, and symptom severity was interpreted as follows: absence of anxiety (0-4), mild anxiety (5)(6)(7)(8)(9), moderate anxiety (10)(11)(12)(13)(14), and severe anxiety (15)(16)(17)(18)(19)(20)(21). Though initially designed to identify generalized anxiety disorder (GAD), the GAD-7 has also been considered as a good screening tool for other common anxiety disorders.…”
Section: • Gad-7mentioning
confidence: 99%
See 2 more Smart Citations
“…All the items were rated on a four-point scale scoring from 0 (not at all) to 3 (nearly every day). The total score ranges from 0 to 21, and symptom severity was interpreted as follows: absence of anxiety (0-4), mild anxiety (5)(6)(7)(8)(9), moderate anxiety (10)(11)(12)(13)(14), and severe anxiety (15)(16)(17)(18)(19)(20)(21). Though initially designed to identify generalized anxiety disorder (GAD), the GAD-7 has also been considered as a good screening tool for other common anxiety disorders.…”
Section: • Gad-7mentioning
confidence: 99%
“…In a recent systematic review of updated prevalence estimates for depression and anxiety from 65 studies, Yufei Li showed a high prevalence of moderate depression and anxiety among health care workers across 21 countries during the COVID-19 pandemic [10], which can negatively impact on the quality of COVID-19 patient care [11]. In Southeast Asia alone, recent evidence has revealed that there seems to be an increasing trend for anxiety and depression over time among healthcare workers compared to the first wave of COVID-19 [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the abundant literature on this subject, few studies specifically analyse the situation in primary care, [11][12][13][14][15] despite the relevant repercussions in this setting and the different characteristics and conditioning factors from those reported in the hospital setting.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, high levels of stress and burnout amongst GPs during the COVID19 pandemic have been reported internationally, with an expanding literature on this topic (e.g. [6][7][8]. Two UK studies of GP pandemic experiences show greater work stress due to rapid change and uncertainty [9] and the importance of teams in creating a sense of solidarity [10].…”
Section: Introductionmentioning
confidence: 99%